Small band-gap-based CNT for modeling of nano sensor - Farhana, Soheli; Alam, A. H. M. Zahirul; Khan, Sheroz (Elsevier Ltd., 2014)
Modeling phenomena of small band-gap Carbon Nanotube (CNT) is analyzed in this paper. Device physics of CNT is studied and do the calculation of sub-band for zigzag CNT to model small band-gap tubes. Each carbon nanotube is illustrated as a single graphite sheet turned round into a cylindrical shape so that the arrangement is one dimensional with axial proportion. A comparison is made with the current literature to show that the proposed chirality CNT with small band-gap which performs the modeling of nano sensor. Furthermore, a sensing device is modeled and discussed in this paper. This carbon nanotube based sensing device makes it possible produce huge amount of nano chips as a disposable cartridge for diagnostic purposes. The optimum CNT is proposed in this paper to model a nano-electrode device. This research outcome shows that the importance of identification with verified uniqueness of high reliability and economical micro-fabrication for cost effectiveness.